PROMOTING DIGITAL DIPLOMACY THROUGH EDUCATION - Victor Adrian VEVERA (Bulletin of "Carol I" National Defense University, 2022)
The implementation of information and communication technologies in the field of international relations has generated important changes, including the emergence of digital diplomacy, which is accompanied by all the challenges of a new beginning. In this article we aim to analyze the extent to which diplomacy is prepared to deal with the contemporary world. In the same we will argue for the need to reconstruct the diplomats' training model so that it can become competitive regardless of the unexpected direction society could follow. From our point of view, the Romanian research organizations (INCD and universities with related specifics) are the ones that must give the directions to follow in conceptualizing the training programs for digital diplomats (including those formed before the emergence of the new platforms and tools dedicated to communication with the public).